Telephone consultations of pediatric patients - how safe is it? - T.K. Mavropulo; S.O. Mokia-Serbina (Zaslavsky O.Yu., 2022)
Background. Telemedicine is defined as "the use of electronic information and communications technologies to provide and support health care when participants are separated" (Field M.J., 1998). The technologies range from standard telephone audio consultations to virtual reality scenarios. The accelerated uptake of telemedicine during the coronavirus disease 2019 pandemic has resulted in valuable experience and evidence on the delivery of telemedicine for pediatric patients. Despite the well-documented benefits of telephone medicine in both triage and disease management, the complexity of medically related telephone communications leaves patients vulnerable to errors in management. The purpose of our work was to describe medical errors related to the use of the telephone during communication between the patient/parents of the patient and the doctor, and the means of countering these errors in pediatrics. Materials and methods. The PubMed Central® database was searched using the keywords "telemedicine", "telephone consultation", "pediatrics", "children", and "patient safety". Results. According to literature, the main types of mistakes were absence of records of the virtual consultation episode, incorrect triage decisions, incorrect diagnosis, failure to recognize the potential seriousness of repeat calls, lack of telephone consultation protocols and insufficient patient information. Measures to increase patient safety were presented: the use of empirical rules and protocols, experience and intuition, taking into account the thoughts and wishes of parents, non-medical factors and the accessibility of health care for the family, the use of a "safety net". Conclusions. Further researches that would examine specific ways of the delivering and use of telemedicine are needed to develop evidence-based guidelines for virtual pediatric care.